Report on Minor Irrigation Works (Maharashtra State) - Planning Commission (Planning Commission, 1963)
The State of Maharashtra forms part of Western India. It comprises the Konkan and Deccan Plateau including Marathwada and’ Vidarbha area. Situated on the western coast and bordering the Arabian Sea, the State extends from latitude I6.4N to 22.1N and longitude 72.6 to 80.9. The State can be divided physically into two unequal parts, i.e. coastal strip of Konkan and Deccan Plateau. The dividing range, commonly called ‘Sahyadri’, runs almost parallel to the Arabian Sea coast at a distance varying from 15 miles to 25 miles from one end of Maharashtra to the other. The crest of this main range has an altitude from 2,000 to 4,500 feet above sea level. Western sea-ward face of this strip is broken in succession. Topography of Konkan is generally undulating giving rise at a number of places to severe soil erosion. Deccan Plateau situated on the eastern side of the ‘Sahyadri’ range slopes gradually from west to east. It has an elevation of about 2,000 feet near the Ghats and 1,400 feet in the central part of Marathwada and Sholapur districts and 900 feet in the south-east of Vidarbha. From eastern flank of ‘Sahyadri’ range several spurs of varying lengths stretch out in eastern direction. These spurs have height of 1,000 to 1,500 feet above the surrounding territory and demarcate different river valleys. A number of rivers traverse this territory. The main streams are Krishna, Wardha, Venganga, Bhima and Godavari. In fact, the whole of Maharashtra State is undulating Plateau with a number of river valleys. The most fertile valleys are, however, situated along rivers Godavari, Bhima and Krishna. The rest of the area is hilly with thin uniform and is marked with undulating topography.
Report on Minor Irrigation Works
Committee on Plan Projects (Irrigation Team), New Delhi